Chapter 19 Concentrated solar energy driven multi-generation systems based on the organic Rankine cycle technology - Desai, Nishith (Taylor & Francis, 2020)
The use of renewable energy sources for multi-generation plants (plants with multiple products, e.g., heat, power, cooling, fresh water) is beneficial to mitigating climate change and to achieving sustainable development. Concentrated solar power plants take advantage of producing heat that can be used for power generation, thermal energy driven refrigeration, desalination, and other heating purposes. Moreover, concentrated solar power plants combined with thermal energy storage provide a cost-effective solution for long-term storage and solve the mismatch problem between supply and demand. For small to medium-scale applications (a few kWe to a few MWe), organic Rankine cycle power systems have been demonstrated to be efficient solutions for multi-generation plants. In this chapter, different concentrated solar power technologies for small to medium-scale applications are reviewed, and multi-generation systems based on the organic Rankine cycle technology are presented. Furthermore, the technical and economic viabilities of using concentrated solar energy powered organic Rankine cycle plants for multi-generation are discussed. Issues related to the system design and integration with different systems (e.g., vapor absorption system for cooling, multi-effect desalination for fresh water generation, etc.) are also addressed.